Association studies of insulin receptor substrate 1 gene (IRS1) variants in type 2 diabetes samples enriched for family history and early age of onset. - Zeggini, E; Parkinson, J; Halford, S; Owen, K; Frayling, T; Walker, M; Hitman, G; Levy, J; Sampson, M; Feskens, E; Hattersley, A; McCarthy, M (2004)
The gene encoding insulin receptor substrate-1 (IRS1) represents a strong biological candidate for a contributory role in type 2 diabetes susceptibility. Indeed, functional studies have implicated the G971R variant, and a recent meta-analysis of 27 association studies suggested that carriage of 971R was associated with a 25% increase in disease risk. However, this association has not been evaluated in large samples. The present study genotyped the P512A and G971R IRS1 variants in 971 U.K. type 2 diabetic subjects ascertained for strong family history and/or early onset, as well as 1,257 control subjects matched by ethnicity. There was no evidence for association with type 2 diabetes for either variant. (For example, the odds ratio [OR] for carriage of 971R was 1.11 [95% CI 0.86-1.44, P = 0.44]) An updated meta-analysis (31 studies: 5,104 case and 7,418 control subjects) remained significant for the G971R association (P = 0.025), albeit with a diminished OR (1.15 [95% CI 1.02-1.31]). Additional studies of IRS1 variation will be required to obtain a robust estimate of the overall contribution of IRS1 variation to type 2 diabetes susceptibility, but the current study suggests that previous studies have overestimated the magnitude of this effect.